Decadal record of continental H 2 reservoirs reveals potential for subsurface microbial life and natural H 2 exploration - Barbara Sherwood Lollar; Oliver Warr (Proceedings of the National Academy of Sciences, 2026)
Interest in the economic potential for hydrogen for decarbonization and the green energy transition is a recent phenomenon. Major questions remain concerning the concentrations, volumes, and sustainability of potential reservoirs, as projections to date are largely theoretical models rather than empirical data. This study integrates previously unpublished long-term data for natural hydrogen production from serpentinization and radiolysis, with research carried out during investigations of the deep subsurface biosphere. The results provide constraints on the volume of natural hydrogen available in the crust and the rates of potential discharge. Discharge rates of >140 tonnes of hydrogen per year from a site in Canada suggest ~4.7 million kwH of energy from hydrogen per year could be available from a single mine location. These data indicate that large discharges of hydrogen may be sustainable in the long-term based on monitoring to date from 1 to >10 y. Calculations from this study site show that the amount of locally generated energy has economic value for both industries and communities located on hydrogen-producing rock. Given that >70% of the continental crust has the potential for hydrogen generation, such local/regional use of this energy source is an unexplored opportunity, in addition expanding our understanding of the habitability of Earth and beyond. We present an alternative vision for the hydrogen economy that can address some of the current challenges arising from the focus to date, that has been largely based on transportation of hydrogen over long distances from source location to markets.